Addressing fundamental behavioural and welfare issues associated with zoo housed animals : using lowland tapirs Tapirus terrestrius and giraffes Giraffa camelopardalis as model species - Kinahan, Anouska Ann (Trinity College (Dublin, Ireland). Department of Zoology, 2002)
Introduction: Zoos, living museums and menageries have been around since early Egyptian and Roman times. Throughout the ages zoos have developed a more important role than merely exhibits. Nowadays, zoos serve a major role in research, conservation and education. As well as zoos themselves changing their function, public perception of zoos has also changed. Due to various wildlife documentaries and the increasing awareness of the continuous destruction to habitat and populations, people are no longer satisfied with seeing wild animals caged in barren and sterile conditions. Increasing knowledge about behaviour also causes concern to the public about the welfare of the animals in captivity (Balmforde et al. 1995)
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin